Peran Koperasi Syariah Dalam Pembangunan Ekonomi Masyarakat Ardirejo - Amaliyah, Angguliyah Rizqi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2024)
Cooperatives are an important role in driving the economy of the community to encourage economic growth. For this reason, this service aims to find out the results of the role of Islamic cooperatives in improving the economic aspects of the Ardirejo community. The method used is through a qualitative descriptive approach and educational studies. The results of the service activities show that Bumi Meranti Wangi Sharia Cooperative located in Ardirejo provides many benefits and opportunities for members in providing financial support through savings and loan activities. Educational studies that refer to the 2019 Subandi Cooperative Economics theory are matched with the results carried out at the Cooperative. So that the achievements of the service activities at this cooperative institution show that the Bumi Meranti Wangi Sharia Cooperative provides convenience for the community in conducting financing based on Islamic law by maintaining the quality of the services provided.